Spread of extensively drug-resistant tuberculosis in KwaZulu-Natal province, South Africa. - Moodley, Prashini; Shah, N Sarita; Tayob, Nabihah; Connolly, Cathy; Zetola, Nicola; Gandhi, Neel; Friedland, Gerald; Sturm, A Willem (PloS one, 2011)
In 2005 a cluster of 53 HIV-infected patients with extensively drug-resistant tuberculosis (XDR-TB) was detected in the Msinga sub-district, the catchment area for the Church of Scotland Hospital (CoSH) in Tugela Ferry, in KwaZulu-Natal province (KZN), South Africa. KZN is divided into 11 healthcare districts. We sought to determine the distribution of XDR TB cases in the province in relation to population density.
Keywords: Antitubercular Agents; Cross-Sectional Studies; Ethambutol; Extensively Drug-Resistant Tuberculosis; Humans; Isoniazid; Kanamycin; Microbial Sensitivity Tests; Ofloxacin; Rifampin; South Africa; Streptomycin